The Evolution Of Academic Vocal Art (Eurasian Scientific Herald, 2026)
This article provides a comprehensive exploration of the historical formation and progressive evolution of vocal performance science, conceptualised as a sophisticated interdisciplinary field that integrates aesthetic artistic expression with rigorous scientific knowledge. The study systematically traces the development of academic vocal art from its initial intuitive origins to the eventual establishment of highly structured pedagogical systems. Particular emphasis is placed on the transformative impact of the Italian bel canto tradition, the pioneering scientific discoveries of Manuel García II, and the foundational methodological contributions provided by both European and Russian vocal schools. The findings demonstrate that the synergistic integration of art and science has significantly enhanced vocal training methodologies, thereby enabling more effective skill acquisition and the preservation of long-term vocal health. Furthermore, the study underscores the critical importance of interdisciplinary competence for contemporary vocal educators, who are increasingly required to synthesise artistic sensitivity with an empirical scientific understanding of the human voice. The prospects for future research in this domain are closely associated with the innovative application of artificial intelligence and personalised digital learning technologies within the framework of modern vocal training